Interpersonal Trust: its relevance for the development of positive emotions and social skills during childhood - Oros, Laura Beatriz (2024)
Identifying the factors that contribute to healthy child development represents a significantchallenge for psychological discipline. This research sought to examine whether interpersonal trustfosters positive emotions and social skills during middle childhood. In this study participated 952Argentine children (52.2 % girls; M age = 10.98 and SD = 1.21) who completed psychometricscales. The sample was selected by availability, according to the possibility of access to schoolinstitutions to carry out the survey. Two factorial MANOVAS were performed to study theinfluence of interpersonal trust and distrust on five positive emotions and four aspects of socialinteraction, respectively. The results indicated that trust promotes joy, sympathy, gratitude,serenity, and personal satisfaction, and distrust inhibits joy but increases sympathy. Also, it wasfound that trust positively influences appropriate social behaviors and reduces aggressiveness,while distrust facilitates aggressiveness, arrogance, and social anxiety. In conclusion, interpersonaltrust provides benefits during middle childhood, as it promotes positive emotional experience andsocial interaction skills; on the contrary, distrust could be considered a risk factor for children’swell-being.